Hubungan Tingkat Nyeri dengan Kualitas Tidur pada Pasien Post Operasi di Rumah Sakit Baladhika Husada Jember - Kazharo, Antik; Hakam, Mulia; Murtaqib, Murtaqib (Pustaka Kesehatan, 2024)
One of the complaints experienced by patients after surgery is postoperative pain. The impact of postoperative pain that is increasingly severe and uncontrolled can disrupt a person's sleep so that it can affect the quality of sleep. The purpose of this study was to determine the relationship between pain level and sleep quality in postoperative patients at the Baladhika Husada Hospital, Jember. The independent variable of this study is the level of pain and the dependent variable is the quality of sleep. This research is a correlational study with a cross sectional approach. Sampling using consecutive sampling technique with 63 respondents. Data collection used NRS and PSQI questionnaire. Data analysis used spearman test with p value <0.05. The results of this study showed that the most pain levels were moderate and the quality of sleep was poor. There is a relationship between pain level and sleep quality in postoperative patients at Baladhika Husada Hospital, Jember (p value = 0.004, r = 0.358). The results showed that the higher the pain level, the higher the quality of sleep. Therefore the role of nurses is very important by providing pharmacological and non-pharmacological therapeutic interventions to overcome and control patient pain so that the sleep disturbance felt by postoperative patients is reduced